Perkembangan Islam di Arab Saudi - Abdullah Abdullah (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
This article discusses Saudi Arabia (Hijaz), in the early 19th century until the beginning of the 20th century free from Western colonialism. Unlike other Muslim countries, almost all of them were colonized by the West. As a result, at that time many scholars and residents from various Muslim countries came to the Hejaz, especially Mecca and Medina. Things like this have caused Saudi Arabia as a country that has the development of Islam to be maintained until now. The results of this study indicate that political changes and religious understandings certainly bring changes in other fields of social culture. Moreover, the beginning of the 19th century was a time when the renewal movement in Islam had only just begun to rise. The reform movement in Islam certainly has a certain impact on the Islamic social life in the Hijaz at that time and in Saudi Arabia today.